EVALUASI KESUBURAN TANAH UNTUK PERTANAMAN TEBU DI KABUPATEN REMBANG, JAWA TENGAH / Evaluation of Soil Fertility to Sugarcane at Rembang District, Central Java - Fitriningdyah Tri Kadarwati (Jurnal Penelitian Tanaman Industri, 2016)
Rembang District is an area of Central Java production center which has the main characteristics dominated by dry land. Dry land issues related to the low availability of water and nutrients. It determines the area of soil fertility conditions. Soil fertility affects the growth, production, and yield of sugarcane. Study of soil fertility conducted through the soil fertility evaluation methods of chemical analysis of matching data criteria soil with soil chemical properties. The sampling method is based on the land unit mapping. Soil fertility assessment based on the analysis of soil chemical properties that include cation exchange capacity (NH4Oac extraction method), pH (pH meter), C-Organic (Walkey and Black method), base saturation (estimation of pH mapping), P2O5 (Olsen and Bray-1 method), and available K (flamephotometer). Soil fertility in Rembang district classified into low until moderate. The limiting factor in soil fertility were consists of nitrogen content, cation exchange capacity, pH, available P2O5, organic carbon, and available K